2007
DOI: 10.1016/j.marenvres.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of meiofauna communities following mudflat disturbance by trampling associated with crab-tiling

Abstract: The provision of artificial shelters for the collection of crabs, known as crab-tiling, and the subsequent harvesting of the soft "peeler" crabs for angling bait, are associated with trampling disturbance of intertidal mudflats in the United Kingdom. Recovery of meiofauna communities following crab-tiling activity was investigated on an intertidal mudflat in SW England. Harvesting of experimental plots was reproduced six times over a 2-week period. Meiofauna was collected at low tides 12h, 36 h and 144 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The number of nematode genera both before and after the habitat loss was generally high and comparable to those of the estuarine intertidal muddy sediments, commonly cited in the literature as mud-adapted (Smol et al, 1994;Soetaert et al, 1995;Steyaert et al, 2007) and typical of the intertidal sediments from the estuarine euhaline section in the Mira estuary (Adão et al, 2009). These assemblages are characterised by high densities of the genera belonging to the families Linhomoeidae (Terschellingia, Linhomoeus), Comesomatidae (Paracomesoma), Desmodoridae (Spirinia) and Axonolaimidae (Odontophora) (Austen and Warwick, 1989;Fisher and Sheaves, 2003;Fonseca et al, 2011;Johnson et al, 2007;Olafsson et al, 2000;Rzeznik-Orignac et al, 2003;Smol et al, 1994;Soetaert et al, 1995;Steyaert et al, 2003;Tietjen, 1977;Wieser, 1960). Nematodes belonging to the aforementioned genera are often tolerant to hypoxic conditions (Jensen, 1984;Steyaert et al, 2007) and their slender bodies may be advantageous to glide through and over the fine sediments (Warwick, 1971), even though some papers have suggested that long slender bodies are more efficient to take up oxygen through diffusion (Fleeger et al, 2011;Soetaert et al, 2002).…”
Section: Discussionmentioning
confidence: 52%
“…The number of nematode genera both before and after the habitat loss was generally high and comparable to those of the estuarine intertidal muddy sediments, commonly cited in the literature as mud-adapted (Smol et al, 1994;Soetaert et al, 1995;Steyaert et al, 2007) and typical of the intertidal sediments from the estuarine euhaline section in the Mira estuary (Adão et al, 2009). These assemblages are characterised by high densities of the genera belonging to the families Linhomoeidae (Terschellingia, Linhomoeus), Comesomatidae (Paracomesoma), Desmodoridae (Spirinia) and Axonolaimidae (Odontophora) (Austen and Warwick, 1989;Fisher and Sheaves, 2003;Fonseca et al, 2011;Johnson et al, 2007;Olafsson et al, 2000;Rzeznik-Orignac et al, 2003;Smol et al, 1994;Soetaert et al, 1995;Steyaert et al, 2003;Tietjen, 1977;Wieser, 1960). Nematodes belonging to the aforementioned genera are often tolerant to hypoxic conditions (Jensen, 1984;Steyaert et al, 2007) and their slender bodies may be advantageous to glide through and over the fine sediments (Warwick, 1971), even though some papers have suggested that long slender bodies are more efficient to take up oxygen through diffusion (Fleeger et al, 2011;Soetaert et al, 2002).…”
Section: Discussionmentioning
confidence: 52%
“…These nematode genera are regularly found in marine shallow waters, but they are particularly abundant in organically enriched silt bottoms (Gyedu-Ababio et al 1999;Fonseca and Netto 2006;Johnson et al 2007). They are all characterized by low oxygen consumption rates (Warwick and Price 1979) and thus, of advantage in oxygen-poor, organically enriched sediments.…”
Section: Discussionmentioning
confidence: 99%
“…One example of this is crab-tiling: Bait collectors lay hard structures (e.g., car tyres and roof tiles) on estuarine mudflats and sand flats to provide shelter for crabs (Sheehan et al 2010a). While the structures may have a positive effect on crabs on a small spatial scale (Sheehan et al 2008), the practice has wider negative impacts on infaunal and bird communities (Johnson et al 2007, Sheehan et al 2010b. At intermediate spatial scales, lobster shelters ('casitas'; Gutzler et al 2015), oyster trestles ( Figure 5C), and crab and lobster pots are contributing to the proliferation of hard structures in the sea and can attract considerable coverage of ephemeral fouling organisms such as barnacles and tube-forming polychaetes (Southward 1995).…”
Section: Structures Associated With Finfish and Shellfish Aquaculturementioning
confidence: 99%